EVALUATING THE EFFECTIVENESS OF NON-PROFIT ORGANIZATIONS ACROSS BORDERS (Neo Scientific Peer Reviewed Journal, 2024)
As the world becomes increasingly interconnected, non-profit organizations (NPOs) have expanded their reach and activities beyond national borders, collaborating with counterparts in different countries and regions. This article examines the effectiveness of the activities undertaken by NPOs in the international arena, exploring the factors that contribute to their success and the challenges they face. Drawing on empirical research and case studies, the study analyzes the operational, financial, and programmatic aspects of cross-border NPO initiatives, highlighting best practices and identifying areas for improvement. The findings provide valuable insights for non-profit leaders, policymakers, and researchers, informing strategies to enhance the impact and sustainability of NPOs' global initiatives.